Performance analysis of exhaust air energy recovery wind turbine / Seyedsaeed Tabatabaeikia - Seyedsaeed , Tabatabaeikia (2016)
Recovering energy from exhaust air systems is an innovative idea. A specific wind turbine generator has been designed in order to achieve this goal. This device consists of two Giromill vertical axis wind turbines (VAWT) combined with four guide vanes and two diffuser plates. The working principle of this design was simulated using the ANSYS Fluent computational fluid dynamics (CFD) package and the results were compared to the experimental ones. The result shows that the optimum position of wind turbine that produces the highest power is when the shaft of the turbine is shifted 150 mm from the centre of discharge outlet. The theoretical analysis also shows that the turbine produces highest power at this position because the positive torque area of the turbine match the highest wind velocity from the cooling tower model. It was perceived from the results that by introducing the diffusers and then the guide vanes, the overall power output of the wind turbine was improved by approximately 5% and 34%, respectively, compared to using VAWT alone. In the case of the diffusers, the optimum angle was found to be 7°, while for guide vanes A and B, it was 70° and 60° respectively. These results were in good agreement with experimental results obtained in the previous experimental study. Overall, it can be concluded that exhaust air recovery turbines are a promising form of green technology. The optimization was carried out in the next step. It was aimed to optimize the overall system energy generation and simultaneously guarantee that it does not violate the cooling tower performance in terms of decreasing airflow intake and increasing fan motor power consumption. The variable factors for the optimization are the wind turbine rotor position, modifying diffuser plates, and the introduction of separator plates to the design. The generated power coefficient was selected as optimization objective. Unlike most of previous optimizations in the field of wind turbines, response surface methodology (RSM) as a method of analytical procedures optimization has been utilised in this study by using multivariate statistic techniques. Both computational and optimization results were validated by experimental data obtained in the laboratory. Results showed that the optimization strategy could improve the wind turbine generated power by 48.6% compared to baseline design. Meanwhile, it is able to enhance the fan intake airflow rate and decrease fan motor power consumption. The obtained optimization equations were also validated by both CFD and experimental results and a very good agreement is achieved.